Orthogonal arraysbased approach to user interfaces testing - Andronova, K.; Kauk, V. («Друкарня Мадрид», 2019)
User Interfaces testing requires the verification of all page elements and controls and their display on a particular screen size and resolution. These days there is a huge variety of devices used by customers and usually those devices have very different screen properties. It causes the problems when creating test cases since this activity requires a big amount of labor costs for running the scope of such test cases created based on all-pairs approach, that is the most usable combinatorial approach for such verifications. So usual activities such as retest and regression testing take a lot of time to complete them.
Keywords: Orthogonal arrays; user interface